2009
DOI: 10.1186/1471-2296-10-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors prompting PSA-testing of asymptomatic men in a country with no guidelines: a national survey of general practitioners

Abstract: Background: Increased use of prostate specific antigen (PSA) has been associated with increased prostate cancer incidence. Ireland is estimated to have one of the highest prostate cancer incidences in Europe and has no national guidelines for prostate cancer screening. GPs have a pivotal role in influencing PSA testing, therefore, our aim was to describe GP testing practices and to identify factors influencing these.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 41 publications
3
44
1
Order By: Relevance
“…Recent surveys in the UK, NI and the RoI suggest that greater disease awareness among the public and health professionals is another factor that may have contributed to decreasing mortality [35][36][37]. For instance, greater awareness of prostate cancer may have led to more systematic PSA testing in men presenting with urinary symptoms or to increasing demand for PSA testing by men with a family history of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent surveys in the UK, NI and the RoI suggest that greater disease awareness among the public and health professionals is another factor that may have contributed to decreasing mortality [35][36][37]. For instance, greater awareness of prostate cancer may have led to more systematic PSA testing in men presenting with urinary symptoms or to increasing demand for PSA testing by men with a family history of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our research among GPs and urologists in NI and the RoI also point to this conclusion. This found that, during the study period, in NI men were unlikely to be referred for biopsy unless their PSA level was greater than 10 ng/ml [38], whereas in the RoI the majority of GPs would refer a man at a PSA level of 7 ng/ml [37]. The younger age at cancer diagnosis of men in the RoI compared with men in NI also supports the hypothesis that men were being investigated more intensively in the RoI for prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the US Preventative Services Task Force stated that men aged 75 years and older, and those younger than 75 years with a life expectancy of less than 10 years should not be screened for prostate cancer, because they are unlikely to benefit [27]. In contrast to these policies, 26% of all baseline tests are being performed in men younger than 50 years and 13% in men [75 years, and our survey of GPs in Ireland found that 34 and 51% of GPs would test asymptomatic men \50 and [75 years, respectively [28]. Year of mortality 1994 1995 1996 1997 1998 1999 2000 2001 2002 2003 2004 2005 1994 1995 1996 1997 1998 1999 2000 2001 2002 2003 2004 2005 1994 1995 1996 1997 1998 1999 2000 2001 2002 2003 2004 2005 1994 1995 1996 1997 1998 1999 2000 2001 2002 2003 2004 2005 Year of incidence Age-standardised rate of prostate cancer incidence/100,000 PSA has both an economic and emotional cost [29,30], and this cost is not trivial [11], either for men themselves, the health services, or society.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 The response rate was probably higher among those physicians who are involved in issues related to PC. The likely direction of possible selection bias is to overestimate the prevalence of PSA test use, if those most actively involved were over-represented among the participants.…”
Section: Discussionmentioning
confidence: 99%